POLA ASUH ORANG TUA BERPENGARUH DI DALAM MENUMBUHKAN PERILAKU POSITIF ANAK - Nuraeni; I Made Sonny Gunawan; Muhamad Suhardi (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2022)
The purpose of this community service activity is to prevent boredom and anxiety for children who are learning from home (BDR) during the Covid-19 pandemic so that they can help their development process properly through the participation of parents. This method of community service activities is carried out through webinars using the Faceebook and Zoom social media flat forms while still paying attention to health protocols from the government. The results obtained in this community service activity were the high enthusiasm of the parents and teachers who participated in the activity. This was evidenced by the large number of participants who participated in the activity and carried out the discussion process by asking questions related to the theme presented.